Fair share and social efficiency: A mechanism in which peers decide on the payoff division - Lu Dong; Rod Falvey; Shravan Luckraz (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
We propose and experimentally test a mechanism for a class of principal-agent problems in which agents can observe each others' efforts. In this mechanism each player costlessly assigns a share of the pie to each of the other players, after observing their contributions, and the final distribution is determined by these assignments. We show that cooperation can be achieved under this simple mechanism and, in a controlled laboratory experiment, we find that players use a proportional rule to reward others in most cases and that the players' contributions improve substantially and almost immediately with 80% of players contributing fully.
Keywords: D62; H41; C79; C90; D63; 330; mechanism design; experimental economics; fairness; distributive justice